E-commerce - Rayport, Jeffrey F.; Jaworski, Bernard J. (Boston : McGraw-Hill/Irwin Marketspace, 2001)
This book is written for present and future practitioners who need a solid foundation in all aspects of conducting business in the New Economy. The authors focus on what a manager needs to know about Internet infrastructure, strategy formulation and implementation, technology concepts, public policy issues, and capital infrastructure in order to make effective business decisions. The book present a framework for the study and practice of e-Commerce with business strategy at the core surrounded by four infrastructures; the technology infrastructure that underlies the Internet, the media infrastructure that provides the content for businesses, public policy regulations that provide both opportunities and constraints, and the capital infrastructure that provides the money and capital to run the businesses. The authors provide a deep exploration of core concepts of New Economy strategy and associated enablers enriched by a wide variety of examples, case studies, and explanations culled directly from practice
Includes bibliographical references and indexes.
lje 20/07/2016
Loans
Keywords: Electronic commerce; Internet advertising; Internet marketing